Circumstances of Confession in Network Society - YAMAGUCHI, Tatsuo (Socio-Informatics, 2021)
This paper is an attempt to critically examine Z. Bauman's description of today's society as “confessional society”. He viewed our everyday uploading to SNS (Social Networking Service) or the Internet as a “confession”.First of all, referring to M. Foucault's discussion, we summarized the characteristics of exagoreusis , which was performed in monasteries in the 4th to 5th centuries, and “confession”, which was performed in Christianity since the Middle Ages. In consequence, it became clear that religious (Christian) “confession” has four characteristics: “power relations”, “speech acts”, “contextual dependence”, and “secrecy”.Next, in order to explore non-religious (non-Christian) confession, we mentioned it which has been drawn in Japanese modern literature. And, we are able to find “power relations” and “speech acts” there.On the other hand, in today's society that rely on the Internet as a technical infrastructure of communication, confession's characteristics are nullified. Because the features of “network” is “flattening”, “datafication”, “de-contextualization”, and “transparentize”. These features conflict with the characteristics of confession, so we can argue that “confession” on SNS or the Internet is become an impossible activity in today's network society.The features of the network suggests that all of information about us is “exposed” on the Internet. We do not confess anything to the Internet, but the “movement” of network is exposing our activity. Therefore, unlike what Bauman pointed out, we should say that today's society is not “confessional society” but “exposure society”.